Young people's experiences of a CDH1 pathogenic variant: Decision‐making about gastric cancer risk management. Issue 1 (15th July 2021) - Hoskins, Cass; Tutty, Erin; Purvis, Rebecca; Shanahan, Mary; Boussioutas, Alex; Forrest, Laura
Abstract: The most effective option for gastric cancer risk management in individuals with a CDH1 germline pathogenic or likely pathogenic variant (PV) in Australia is prophylactic total gastrectomy (PTG). There is, however, increasing confidence in endoscopic surveillance as a risk management strategy thus affording individuals with a CDH1 PV with challenging decisions regarding their gastric cancer risk management. For young people, this decision‐making comes at a complex development stage of emerging and young adulthood. This study aims to explore the factors that influence young people's decision‐making about their gastric cancer risk management due to a CDH1 PV. Potential participants were identified and approached through the Parkville Familial Cancer Centre in Melbourne, Australia. Thematic analysis was used to interpret and analyze the data. Qualitative interviews were conducted with 13 people with a CDH1 PV aged 18 to 39 years, inclusive. The interviews found that participants' familial and shared experiences of cancer and risk management, perceived tolerance of uncertainty, and desire for control over their cancer risk were fundamental in their decision‐making about their gastric cancer risk management. The participants' young adult life stage was also deemed particularly important in decisions about the timing of PTG. The findings of this study are vital to inform decisional counseling discussions with this unique population.